2017
DOI: 10.1049/iet-pel.2016.0437
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase optimal injection PWM with dual carrier frequency to reduce current THD

Abstract: Multiphase voltage source inverter drives have recently applied to various industrial applications for variable speed motor drives. Both space-vector pulse-width modulation (SVPWM) and discontinuous PWM (DPWM) are commonly used modulators. Under the three-phase setting, it is well known that SVPWM is preferred for small modulation indices, whereas DPWM is better for large modulation indices. However, little detailed discussions on multiphase setting are reported. Further, for phase number higher than 5, no exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…In the previous section, it has been shown that the three formulas (4), (9), and (11) can be used for keeping the average AC capacitor charge constant through 60° Flat-Top transitions. The actual algorithm using these formulae can be designed based on Figs.…”
Section: Compensation Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous section, it has been shown that the three formulas (4), (9), and (11) can be used for keeping the average AC capacitor charge constant through 60° Flat-Top transitions. The actual algorithm using these formulae can be designed based on Figs.…”
Section: Compensation Algorithmmentioning
confidence: 99%
“…6 and 9, ΔD 2 correction is added to the same phase leg duty ratio for type 2 transitions both before and after the transition, but the direction of the correction (sign) is different. As the compensation has been calculated for positive zero-sequence steps in (9) and (11), the sign of ΔD 1 also needs to be inverted for negative zero-sequence steps shown in Table 1.…”
Section: Compensation Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-frequency harmonics will cause current waveform distortion, motor heating, motor vibration, efficiency decrease and degradation of the control performance. More importantly, since the carrier frequency is usually at the range between 2 and 20 kHz, which overlaps with the human ear audible range, the noise induced by carrier frequency harmonics is a restriction for SVPWM application, such as elevators or electric vehicles [13]. Increasing the switching frequency will lead to a lower size of inductance and capacitance, which will lead to a size reduction in the control board while it means higher switching loss and more expensive switching elements.…”
Section: Introductionmentioning
confidence: 99%
“…It can be evidently investigated that, the space vector pulse width modulation (SVPWM) is the most widely applied scheme. SVPWM has attractive flexibility for optimizing switching waveforms and is convenient to implement on embedded processors [10,11], as well as its operational advantages over carrier-based techniques (i.e., low total harmonic distortion, high efficiency and voltage available in the DC-link) [12].…”
Section: Introductionmentioning
confidence: 99%